2009
DOI: 10.1002/hep.22737
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated fatty acids inhibit the expression of tumor suppressor phosphatase and tensin homolog (PTEN) via microRNA-21 up-regulation in hepatocytes # †

Abstract: P hosphatase and tensin homolog (PTEN) is a protein and phosphoinositide phosphatase originally identified as a tumor suppressor gene frequently mutated/deleted in human cancers. 1 Numerous studies have also strongly supported its role as a regulator of insulin/insulin-like growth factor 1 signaling. 2 In mice, liver-specific PTEN deletion leads to steatosis, insulin hypersensitivity early in life, and hepatomegaly and hepatocellular carcinoma (HCC) at later stages. 3,4 Consistent with these studies, PTEN is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
135
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(149 citation statements)
references
References 40 publications
12
135
1
1
Order By: Relevance
“…40 The increased expression of levels of miR-200a, miR-200b, miR-429, belonging to the same genomic cluster, were found in our model of NAFLD, and it is in agreement with other studies. 26,27 Contrarily from that observed by Vinciguerra et al, 41 but equally to Li et al, 26 we observed a significant downregulation of miR-21 that seems to be unrelated to PTEN expression, but to other potential targets such as LITAF. Recently, an interesting role in liver fibrogenesis was attributed to the upregulation of miR-27a and miR-27b 42 ; in our model, the downregulation of miR-27a appears mainly associated to the inflammatory molecules and fatty acid metabolism.…”
Section: Discussionsupporting
confidence: 82%
“…40 The increased expression of levels of miR-200a, miR-200b, miR-429, belonging to the same genomic cluster, were found in our model of NAFLD, and it is in agreement with other studies. 26,27 Contrarily from that observed by Vinciguerra et al, 41 but equally to Li et al, 26 we observed a significant downregulation of miR-21 that seems to be unrelated to PTEN expression, but to other potential targets such as LITAF. Recently, an interesting role in liver fibrogenesis was attributed to the upregulation of miR-27a and miR-27b 42 ; in our model, the downregulation of miR-27a appears mainly associated to the inflammatory molecules and fatty acid metabolism.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies have also shown that macrophages actively intake exosomes containing miR molecules, which could be another way of delivering the regulatory message of the miRs from one cell to another (Lasser, et al 2011). According to Vinciguerra et al (2009) the up-regulation of miR-21…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanisms underlying the NF-κB effect are not clear. PDCD4 is negatively regulated by miR-21 (23), and at least in myeloma cells, miR-21 expression is regulated by NF-κB (36,37). We therefore hypothesized that NF-κB might regulate β cell death through miR-21 and PDCD4.…”
Section: Pdcd4 Deficiency Prevents Islet β Cell Death Whereas Pdcd4mentioning
confidence: 99%